The Classpoint Utilization Training in Supporting differentied Instruction For Teacher of SMP 21 Dumai: Pelatihan Pemanfaatan Classpoint dalam Mendukung Pembelajaran Terdiferensiasi bagi Guru SMP Negeri 21 Dumai - Mustika, Tria Putri; Andhi, Rahmat Rizal Andhi; Sari, Filma Alia Sari; Charlina, Charlina; Faizah, Hasnah Faizah; Sinaga, Mangatur Sinaga (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
The results of the situation analysis show that the implementation of differentiated learning at SMPN 21 Dumai is not yet optimal, this is proven by the content indicators that teachers still depend on the material in books. Based on the problems faced, the solution that can be presented is Classpoint-Based Learning Media Training to Realize Differentiated Learning. The results of the training showed that of the 25 participants who developed learning media, 11 people or 44% of participants achieved very good criteria, 12 participants or 48% achieved good criteria, and 2 people or 8% of participants achieved low criteria. If we look at the overall average score, the Classpoint Teacher learning media training participants at SMP Negeri 21 Dumai achieved very good criteria, namely a score of 85.3%. Thus, the Classpoint Utilization training for Dumai 21 Public Middle School teachers can be said to be successful. Classpoint-based learning media training is a strategic step in supporting differentiated learning. By utilizing technology, teachers can more effectively meet students' unique needs, creating inclusive and engaging learning environments